Use of the Semantic Differential in Bilingualism Research and its Relevance to Translation - Romney, David; Bynner, John (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1981)
AbstractTo investigate bilingual subjects' perceptions of the connotative differences between concepts in English and French, a form of the semantic differential was employed in which the scales were derived from Cattell's 16 personality factors. Altogether 16 concepts were rated and these were made up of four sets, each set containing a pair of synonyms in English and a pair of synonyms (their translation-equivalents) in French. Even though the sets themselves were easily distinguishable in terms of their affective meaning, no significant differences in affective meaning emerged between the concepts in any of the sets either within or across languages. There were, however, significant differences between individuals in the ways they perceived the concepts. Some of these differences seemed to be due to the effects of dominant language, A cluster analysis of the individuals in terms of the semantic difference between concepts and their translation-equivalents (over and above the difference between synonyms) gave little support to the postulated distinction between the two types of bilingual, compound and coordinate, although there was some evidence that the compound bilingual exists as a separate type.